Hirschsprung disease in twins: A case series - Kelly Banh; Rebecca Moreci; Hans Andersson; Jessica A. Zagory (Elsevier, 2023)
Introduction: Hirschsprung's disease (HD) occurs secondary to failed migration of neural crest cells in embryonic life and results in a dysfunctional, mechanically obstructed colon. Despite an increased occurrence amongst family members, predominantly amongst siblings, HD in twins is extremely rare with approximately 21 total cases documented in the literature. Case presentations: This case series includes 2 cases of concordant expression of HD in twins: one dizygotic set and the other monozygotic. This is contrary to prior studies which suggest that monozygotic twins more frequently exhibit disease discordance, where one twin is affected while the other is not, over disease concordance. In each case, the twins demonstrated either variability in presentation or location of pathology, which ultimately delayed diagnosis and further management. The complex etiology makes it difficult to predict the likelihood of disease inheritance. A comprehensive literature review is also included to consider the rarity of this occurrence and evaluate the variation of concordant disease expression. Conclusion: Further understanding of the inheritance pattern will help guide management and provide us with more information for genetic counseling.